Cuba's military 1990-2005 : Revolutionary soldiers during counter-revolutionary times - Klepak, H. P. (Studies of the Americas., 2005)
Provides an examination of the Cuban military in the context of Cuba's political and economic challenges in the aftermath of the collapse of the USSR, and therefore of Soviet economic, political and psychological support. This book does so by providing historical and political contexts of the development and engagement of the military.